Density estimation for dynamic volumes - Fuchs, Christian; Chen, Tongbo; Goesele, Michael; Theisel, Holger; Seidel, Hans-Peter (Computers & graphics, 2007)
We propose a new approach to capture the volumetric density of dynamic scattering media instantaneously with a single image. The volume is probed with a set of laser lines and the scattered intensity is recorded by a conventional camera. We then determine the density along the laser lines taking the scattering properties of the media into account. A specialized approximation technique reconstructs the full density field in the volume. We apply the technique to capture the volumetric density of participating media such as smoke.